2013
DOI: 10.1071/an12374
|View full text |Cite
|
Sign up to set email alerts
|

Natural plant extracts and prebiotic compounds as alternatives to antibiotics in broiler chicken diets in a necrotic enteritis challenge model

Abstract: Abstract. An experiment was conducted to determine the effects of two different water-soluble carbohydrate extracts (renga renga lily extract and Acacia extract), and two commercially available prebiotic compounds, Fibregum and Raftifeed-IPE, on the performance of broiler chickens subjected to a necrotic enteritis (NE) challenge model. These treatments were compared with negative control and a positive (Zn-bacitracin) control treatments. An overall 8.8% NE-related mortality was recorded, with mean jejunal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…The Yeast and Sangrovit treated groups showed a significant decrease in the total coliform count of intestinal content in comparison to t he control group This result agreed with Natsir et al (2013); Vidanarachchi et al (2013) and Boka et al (2014). Table 7: The effect of dietary supplementation of Yeast and Sangrovit on the coliform bacterial count in healthy and E.coli experimentally infected groups at 4 and 6 weeks of age( means ± standard error (SE); n=20).…”
Section: Resultssupporting
confidence: 71%
“…The Yeast and Sangrovit treated groups showed a significant decrease in the total coliform count of intestinal content in comparison to t he control group This result agreed with Natsir et al (2013); Vidanarachchi et al (2013) and Boka et al (2014). Table 7: The effect of dietary supplementation of Yeast and Sangrovit on the coliform bacterial count in healthy and E.coli experimentally infected groups at 4 and 6 weeks of age( means ± standard error (SE); n=20).…”
Section: Resultssupporting
confidence: 71%
“…Liu et al [ 152 ] found that dietary supplementation of exogenous lysozyme decreased the C. perfringens colonization and improved the intestinal barrier function of chickens. Furthermore, it was demonstrated that a prebiotic product (arabinogalactan Fibregum) was effective in controlling NE [ 153 ].…”
Section: Restoration Of the Impaired Barrier Functionmentioning
confidence: 99%
“…The functional competence and metabolic profile of body fluids and tissues can change in response to feed additives used. Reviews published recently have highlighted herbal plants as dietary supplements (26), among them alfalfa preparation (2,3). Recent studies have underlined its effectiveness on sheep (21,29), turkeys (19), laying hens (12), broiler chickens (8), and finally, pigs (14,15,22), where low alfalfa protein concentrate (APC) supplementation in the 2% -3% range caused higher weight gains and better feed conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Its utility can be evaluated on the basis of swine performance and blood metabolic profile (10). Some authors (26,31) indicate alternate periods of supply and withdrawal of phytogenic preparations because of the manner of their metabolising and the effect of numerous biologically active compounds on the gastrointestinal tract microbiome as well as the blood metabolic profile in humans and animals. In the available sources, there are only few data on the effectiveness of APC on swine performance and health and therefore further studies are still needed in this area.…”
Section: Introductionmentioning
confidence: 99%